A Cluster Randomized Controlled Trial to Reduce Office Workers' Sitting Time: Effect on Activity Outcomes. Issue 9 (September 2016) - HEALY, GENEVIEVE N.; EAKIN, ELIZABETH G.; OWEN, NEVILLE; LAMONTAGNE, ANTHONY D.; MOODIE, MARJ; WINKLER, ELISABETH A. H.; FJELDSOE, BRIANNA S.; WIESNER, GLEN; WILLENBERG, LISA; DUNSTAN, DAVID W.
ABSTRACT: Purpose: This study aimed to evaluate the initial and long-term effectiveness of a workplace intervention compared with usual practice, targeting the reduction of sitting on activity outcomes. Methods: Office worksites (≥1 km apart) from a single organization in Victoria, Australia, were cluster randomized to intervention ( n = 7) or control ( n = 7). Participants were 231 desk-based office workers (5–39 participants per worksite) working at least 0.6 full-time equivalent. The workplace-delivered intervention addressed organizational, physical environment, and individual behavioral changes to reduce sitting time. Assessments occurred at baseline, 3 months, and 12 months, with the primary outcome participants' objectively measured (activPAL3 TM device) workplace sitting time (minutes per 8-h workday). Secondary activity outcomes were workplace time spent standing, stepping (light, moderate to vigorous, and total), and in prolonged (≥30 min) sitting bouts (hours per 8-h workday); usual duration of workplace sitting bouts; and overall sitting, standing, and stepping time (minutes per 16-h day). Analysis was by linear mixed models, accounting for repeated-measures and clustering and adjusting for baseline values and potential confounders. Results: At baseline, on average, participants (68% women; mean ± SD age = 45.6 ± 9.4 yr) sat, stood, and stepped for 78.8% ± 9.5%, 14.3% ± 8.2%, and 6.9% ± 2.9% of work hours, respectively. Workplace sitting time was significantly reduced in the intervention group compared with the controls at 3 months (−99.1 [95% confidence interval = −116.3 to −81.8] min per 8-h workday) and 12 months (−45.4 [−64.6 to −26.2] min per 8-h workday). Significant intervention effects (all favoring intervention) were observed for standing, prolonged sitting, and usual sitting bout duration at work, as well as overall sitting and standing time, with no significant or meaningful effects observed for stepping. Conclusions: This workplace-delivered multicomponent intervention was successful at reducing workplace and overall daily sitting time in both the short term and the long term. Abstract : Supplemental digital content is available in the text.